Blow-Up of the Solution for a Semilinear Parabolic Problem with a Mixed Source - Wai Yuen Chan (Mathematics, 2022)
A semilinear parabolic equation with the Dirichlet boundary condition is examined. The reaction source is a mixed nonlinear function. This paper investigates the existence and uniqueness of a solution. A sufficient condition for the solution being blow-up in finite time is found.